Identification and Characterization of Glycoproteins on the Spore Surface of Clostridium difficile - Strong, Philippa C. R. (American Society for Microbiology, 2014)
In this study, we identify a major spore surface protein, BclA, and provide evidence that this protein is glycosylated. Following extraction of the spore surface, solubilized proteins were separated by one-dimensional PAGE and stained with glycostain to reveal a reactive high-molecular-mass region of approximately 600 kDa. Tandem mass spectrometry analysis of in-gel digests showed this band to contain peptides corresponding to a putative exosporangial glycoprotein (BclA3) and identified a number of glycopeptides modified with multiple N-acetyl hexosamine moieties and, in some cases, capped with novel glycans. In addition, we demonstrate that the glycosyltransferase gene sgtA (gene CD3350 in strain 630 and CDR3194 in strain R20291), which is located immediately upstream of the bclA3 homolog, is involved in the glycosylation of the spore surface, and is cotranscribed with bclA3. The presence of anti-β-O-GlcNAc-reactive material was demonstrated on the surface of spores by immunofluorescence and in surface extracts by Western blotting, although each strain produced a distinct pattern of reactivity. Reactivity of the spore surface with the anti-β-O-GlcNAc antibody was abolished in the 630 and R20291 glycosyltransferase mutant strains, while complementation with a wild-type copy of the gene restored the β-O-GlcNAc reactivity. Phenotypic testing of R20291 glycosyltransferase mutant spores revealed no significant change in sensitivity to ethanol or lysozyme. However, a change in the resistance to heat of R20291 glycosyltransferase mutant spores compared to R20291 spores was observed, as was the ability to adhere to and be internalized by macrophages.